2008
DOI: 10.1007/s12020-008-9095-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and epidemiological characteristics of thyroid hemiagenesis: ultrasound screening in patients with thyroid disease and normal population

Abstract: Thyroid hemiagenesis is a rare form of thyroid dysgenesis, in which one thyroid lobe fails to develop. The true prevalence of this rare abnormality is about 0.05-0.2% in normal population. We aimed to determine prevalence of thyroid hemiagenesis in patients with various thyroid disorders and a normal population in a mild to moderate iodine-deficient area. The clinical and thyroid ultrasonography records of 4,833 patients who presented with various thyroid disorders were reviewed. In addition, ultrasonographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…The fact that diagnosis of THA is often made when some other thyroid disease is present, coupled with the paucity of cases without overt thyroid disorder under observation, makes assessment of the outcome of patients affected with this anomaly very difficult. However, the latest analysis of Gursoy et al revealed that the incidence of THA among patients with thyroid disorders is tenfold greater than in the healthy population, supporting our conclusion that subjects with THA are more prone to develop thyroid disorders (16).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The fact that diagnosis of THA is often made when some other thyroid disease is present, coupled with the paucity of cases without overt thyroid disorder under observation, makes assessment of the outcome of patients affected with this anomaly very difficult. However, the latest analysis of Gursoy et al revealed that the incidence of THA among patients with thyroid disorders is tenfold greater than in the healthy population, supporting our conclusion that subjects with THA are more prone to develop thyroid disorders (16).…”
Section: Discussionsupporting
confidence: 87%
“…The only concomitant thyroid abnormalities described in this largely pediatric cohort were nodules and cysts, while immunological tests were not performed (19). The latest study of 14 subjects by Gursoy et al revealed the presence of associated thyroid pathology in nine patients, of whom four patients were diagnosed with Hashimoto's thyroiditis, four patients with a nontoxic multinodular goiter, and one patient with toxic adenoma (16). The observed variety of thyroid pathological entities overlapping THA suggests a strong impact of environmental factors, age structure, and the selection of the analyzed group on the clinical profile of patients with THA.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…al, (7) it is a complete and congenital absence of the thyroid isthmus.In studies the prevalence of the thyroid hemiagenesis ranged between 00.5-0.2%. Most commonly seen in women and as left lobe agenesis (8)(9)(10) The thyroid isthmus agenesis is uncommon and we recognized the absence of isthmus incidentally during surgery. Operations memories are presented in figure 2 and figure 3.…”
Section: Case Reportmentioning
confidence: 85%
“…Thyroid isthmus agenesis is not a situation where surgeons often encounter. When USG looked carefully, isthmus agenesis can be seen and this can help in surgery (8).…”
Section: Case Reportmentioning
confidence: 99%